1997
DOI: 10.1164/ajrccm.155.4.9105075
|View full text |Cite
|
Sign up to set email alerts
|

Maximal inspiratory pressures and dimensions of the diaphragm.

Abstract: We postulated that the variation of maximal voluntary inspiratory pressures (PI,max and Pdi,max) among individuals largely reflects the variation of the structural attributes of the inspiratory muscles, in particular the muscular cross-sectional area of the diaphragm (CSAdi) and its axially projected area (A(thor)). To test this postulate, we measured PI,max in 36 healthy subjects, including 3 children and 15 weight-lifters, and Pdi,max in 11 subjects. Structural measurements by ultrasonography and anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 0 publications
5
66
1
Order By: Relevance
“…In addition, differences in physiological variables such as thoracoabdominal configuration, differences in the study group and technical issues are suggested to be responsible, at least in part, for the high between-subject variability. Furthermore, the variation in inspiratory pressures has been attributed to the variation in diaphragm thickness [25]. Some published regression equations are even in disagreement, since, for example, height has been shown to be positively predictive [8,14,15], negatively predictive [13] and not predictive [5,9,11,16] for PI,max, and the number of variables included in the final model of the regression equation following stepwise regression varies significantly [5,8,9,11,[13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, differences in physiological variables such as thoracoabdominal configuration, differences in the study group and technical issues are suggested to be responsible, at least in part, for the high between-subject variability. Furthermore, the variation in inspiratory pressures has been attributed to the variation in diaphragm thickness [25]. Some published regression equations are even in disagreement, since, for example, height has been shown to be positively predictive [8,14,15], negatively predictive [13] and not predictive [5,9,11,16] for PI,max, and the number of variables included in the final model of the regression equation following stepwise regression varies significantly [5,8,9,11,[13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a number of authors have assessed the respiratory muscles in humans, especially the diaphragm, using the ultrasound technique [10][11][12][13]. Both in M-mode and B-mode, ultrasound provides an alternative to other more sophisticated techniques, such as computed tomography, for assessing thickness, configuration and displacement of the diaphragm [16].…”
Section: Background and Validity Of The Methodsmentioning
confidence: 99%
“…This method has been shown reliably to measure changes in diaphragm thickness during contraction [10,11] and has been used to assess the relationship between lung volume and diaphragmatic thickness [10,[12][13][14]. In contrast, to our knowledge, ultrasonographic data on abdominal muscles in humans are scarce both for normal subjects [5,6] and for a number of respiratory diseases in which abdominal muscles contribute importantly to respiration [8].…”
Section: In N V Vi Iv Vo O U Ul Lt Tr Ra As So Ou Un Nd D Amentioning
confidence: 99%
“…While MIP measures the strength of inspiratory muscle contraction, MEP measures expiratory muscle strength. (15,16) Previous studies have shown that the variation of MIP among individuals reflects the variation of the structural attributes of the inspiratory muscles, in particular the muscular cross-sectional area of the diaphragm, (17)(18)(19) and that adults with asthma have reductions of up to 30% in maximal respiratory pressures as a result of the effects of hyperinflation. (20) Measurement of maximal respiratory pressures is very well known and also widely used to assess children with chronic lung disease; however, there are questions about the value of respiratory muscle strength in this group of patients.…”
Section: Introductionmentioning
confidence: 99%